Caffeine and Progression of Parkinson Disease. Issue 5 (September 2015) - Simon, David K.; Wu, Cai; Tilley, Barbara C.; Wills, Anne-Marie; Aminoff, Michael J.; Bainbridge, Jacquelyn; Hauser, Robert A.; Schneider, Jay S.; Sharma, Saloni; Singer, Carlos; Tanner, Caroline M.; Truong, Daniel; et al.
<x xml:space="preserve">Abstract</x> Objective Increased caffeine intake is associated with a lower risk of Parkinson disease (PD) and is neuroprotective in mouse models of PD. However, in a previous study, an exploratory analysis suggested that, in patients taking creatine, caffeine intake was associated with a faster rate of progression. In the current study, we investigated the association of caffeine with the rate of progression of PD and the interaction of this association with creatine intake. Methods Data were analyzed from a large phase 3 placebo-controlled clinical study of creatine as a potentially disease-modifying agent in PD. Subjects were recruited for this study from 45 movement disorders centers across the United States and Canada. A total of 1741 subjects with PD participated in the primary clinical study, and caffeine intake data were available for 1549 of these subjects. The association of caffeine intake with rate of progression of PD as measured by the change in the total Unified Parkinson Disease Rating Scale score and the interaction of this association with creatine intake were assessed. Results Caffeine intake was not associated with the rate of progression of PD in the main analysis, but higher caffeine intake was associated with significantly faster progression among subjects taking creatine. Conclusions This is the largest and longest study conducted to date that addresses the association of caffeine with the rate of progression of PD. These data indicate a potentially deleterious interaction between caffeine and creatine with respect to the rate of progression of PD.